Studi Pengetahuan Dan Perilaku Siswa SD YPK III Bethel Doom Dalam Pengelolaan Sampah Di Wilayah Lingkungan Doom Barat - Manurung, Melani; Widya Yanti, Dwi Indah; Masengi, Melisa; Tabalessy, Roger R.; Sahuleka, Matheos Dedi; Siwabessy, Aldomoro; Br Gultom, Dormauli (Innovative: Journal Of Social Science Research, 2024)
Objective in this study is to determine how students' knowledge about the cleanliness of the school environment, student attitudes and student behavior about the cleanliness of the school environment school. The population used in this study were elementary school students at YPK III Bethel Doom Elementary School. elementary school students at SD YPK III Bethel Doom. The research was conducted in October - November 2023, using the method ( purposive sample) with the basis of consideration is to take 5th and 6 th grade students as the main informants and based on the facilities owned in the school. As the main informant and based on the facilities owned at the school and suitable for research and suitable for research. Based on the results research results obtained related to Knowledge Waste Management in YPK III Bethel Doom Elementary School Students that waste management in the elementary school environment is classified as very good. This is indicated by the acquisition of values on the questionnaire is above the average value. While student behavior regarding waste management in the SD environment YPK III Bethel Doom is classified as very good. This is shown by the lack of garbage in the elementary school environment. The result of data analysis data analysis results obtained correlation between the two variables of attitude and knowledge <0.003 with sig (t.tailed) 0.493, it shows that the correlation between variables is significant. Or it can be concluded that there is a relationship between student knowledge and student behavior.